Modeling the implications of sustainable supply chain practices on sustainable performance in Ghana's petroleum industry: the role of stakeholders' pressure. Issue 1 (31st December 2022) - Karikari Appiah, Michael; Boateng, Frederick; Abugri, Alex; Barnes, Samuel
ABSTRACT: The influx of Agenda 2030 for Sustainable Development and the COP 21 has necessitated the need for a paradigm shift in traditional consumption and production to reflect a balance between environmental safety, social justice and profitability. The Ghanaian Petroleum Industry is predominately fossil fuel–based with higher level of carbon and methane emissions. Ensuing from the Stakeholders' and the Resource-Based View theories, this paper aims to develop a model to explain the relationship between sustainable supply chain management (SSCM) practices and sustainable performance (SP) by examining the extent to which pressure from stakeholders could strengthen the proposed model in the context of downstream petroleum supply chain. Variance-Based Partial Least Square method has been used to analyse a cross-sectional data from Oil Marketing companies in Ghana. Our results have revealed that SSCM practices such as environmental, economic, and social are positively related to SP. Moreover, stakeholder's pressure positively and significantly relates to SP. Again, stakeholders' pressure significantly moderate the relationships between environmental and social dimensions of SSCM practices and SP. By implications, there is an emergency of an SP model with enhanced predictability. Again, policymakers and advocates can achieve greater sustainability by maximising stakeholders' pressure.